2021
DOI: 10.3389/fcvm.2021.743868
|View full text |Cite
|
Sign up to set email alerts
|

Common Polymorphisms in the RGMa Promoter Are Associated With Cerebrovascular Atherosclerosis Burden in Chinese Han Patients With Acute Ischemic Cerebrovascular Accident

Abstract: Repulsive guidance molecule a (RGMa) plays a vital role in the progression of numerous inflammatory diseases. However, whether it participates in atherosclerosis development is not known. Here, we explored the influence of RGMa in atherogenesis by investigating whether an association exists between functional polymorphisms in the RGMa promoter and cerebrovascular atherosclerosis burden (CAB) in Chinese Han patients diagnosed with acute ischemic cerebrovascular accident. To this end, we conducted a genetic asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The evaluation of RGM-A as an immunoregulatory protein has recently increased in translational medical research, especially with regard to peritonitis (21, 22) and acute lung injury (23,24). In our previous study, we found that the RGM-A level was reduced in atherosclerotic aortas and in macrophages isolated from plaques, suggesting that RGM-A has a potential protective effect in cerebrovascular atherosclerosis (20). Previous researchers have demonstrated that RGM-A is expressed in pathogenic Th17 cells in experimental autoimmune encephalomyelitis (18), and the binding of RGM-A to its receptor neogenin inhibits PMN migration and increases the attachment of CD4+ cells to intercellular adhesion molecule-1 to attenuate the inflammatory response (18,21,22).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The evaluation of RGM-A as an immunoregulatory protein has recently increased in translational medical research, especially with regard to peritonitis (21, 22) and acute lung injury (23,24). In our previous study, we found that the RGM-A level was reduced in atherosclerotic aortas and in macrophages isolated from plaques, suggesting that RGM-A has a potential protective effect in cerebrovascular atherosclerosis (20). Previous researchers have demonstrated that RGM-A is expressed in pathogenic Th17 cells in experimental autoimmune encephalomyelitis (18), and the binding of RGM-A to its receptor neogenin inhibits PMN migration and increases the attachment of CD4+ cells to intercellular adhesion molecule-1 to attenuate the inflammatory response (18,21,22).…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, this study is the first to show that the plasma RGM-A level is decreased in patients with SAP. RGM-A is a promising target for the diagnosis and treatment of numerous diseases based on its versatility; it is involved in ischemic stroke (35), Parkinson's disease (36), autoimmune encephalomyelitis (18), multiple sclerosis (19), and cerebrovascular atherosclerosis (20). The evaluation of RGM-A as an immunoregulatory protein has recently increased in translational medical research, especially with regard to peritonitis (21, 22) and acute lung injury (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations